Evaluation of antibacterial activities and toxicity of licuala spinosa's fruits / Nur Izzati Zakaria - Zakaria, Nur Izzati (Faculty of Applied Sciences, 2014)
Licuala spinosa (Arecaceae) was used by the natives in Malaysia to treat centipede bites and act as antidote to poisoning. An evaluation on the antibacterial and acute toxicity activity of the extract of this plant is crucial to support the therapeutic claims. The extract was prepared through the maceration of dried powdered fruits using 70% methanol. It was tested against five different concentrations which were 25 mg/ml, 50 mg/ml, 100 mg/ml, 200 mg/ml and 400 mg/ml of distilled water. The vancomycin was served as positive control while methanol was used as negative control. The methanolic extract of L.spinosa's fruit was tested on gram negative bacteria (Pseudomonas aeruginosa and Escherichia coli) and gram positive bacteria (Bacillus substilis and Micrococcus luteus) by using disc diffusion method. The results showed that the extract has the highest antibacterial activity on B. Substilis at concentration 400 mg/ml with zone inhibition of 10. 7 mm. For gram negative bacteria,extract showed the highest antibacterial activity on P. aeruginosa at concentration 400 mg/ml with zone inhibition of 4.3 mm. Then, the methanolic extract of L.spinosa 's fruits was tested using brine shrimp lethality test. The LC50 was lesser than l .0mg/ml in which was known to possess toxic effect. The maximum mortality took place at concentration 200 μg/ml which is 86% mortality rate whereas there is no mortality observed at 10 μg/ml.